2022
DOI: 10.2196/28783
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Unmet Needs for Mobile Technology Among Hospitalists: Workflow Analysis Based on Semistructured Interviews

Abstract: Background The hospitalist workday is cognitively demanding and dominated by activities away from patients’ bedsides. Although mobile technologies are offered as solutions, clinicians report lower expectations of mobile technology after actual use. Objective The purpose of this study is to better understand opportunities for integrating mobile technology and apps into hospitalists’ workflows. We aim to identify difficult tasks and contextual factors tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Though a more complete and structured digital documentation has been achieved by the process implementation, it can still be optimized with respect to daily clinical practice. The potential to reduce workflow time through digitalization [3] could not yet be exploited regarding documentation, while reaching a noticeable improvement in data access time.…”
Section: Discussionmentioning
confidence: 99%
“…Though a more complete and structured digital documentation has been achieved by the process implementation, it can still be optimized with respect to daily clinical practice. The potential to reduce workflow time through digitalization [3] could not yet be exploited regarding documentation, while reaching a noticeable improvement in data access time.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of electronic health records readily available at the bedside further hinders an already complex workflow. Research of hospitalists, including advanced practice nurses, indicated that the use of mobile apps could be most beneficial in enhancing team-based communication and care coordination 15. As more healthcare systems move toward team-based care to provide greater efficiency for achieving better patient outcomes and caregiver satisfaction, communication will become even more important for effective coordination and collaboration among healthcare team members 14,16.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research of hospitalists, including advanced practice nurses, indicated that the use of mobile apps could be most beneficial in enhancing teambased communication and care coordination. 15 As more healthcare systems move toward teambased care to provide greater efficiency for achieving better patient outcomes and caregiver satisfaction, communication will become even more important for effective coordination and collaboration among healthcare team members. 14,16 Key content areas for consideration in the development of innovative technology include the following:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies indicate that EHRs make it easier for health care providers to organize and access information, including physicians [ 15 ], residential staff in aged care facilities [ 16 ], and residential staff in agencies serving individuals with intellectual disabilities [ 17 ]. However, unfortunately, EHRs have actually decreased physician efficiency and hindered workflow because of the difficulty in recording patient data [ 18 ]. Providers often need to remember patient information or document it via paper and pencil until they are able to access a computer to enter it into the EHR [ 19 ], which can increase the likelihood of human error and inaccurate data [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Providers often need to remember patient information or document it via paper and pencil until they are able to access a computer to enter it into the EHR [ 19 ], which can increase the likelihood of human error and inaccurate data [ 20 ]. Furthermore, physicians reported that usability issues, slow system response times, information overload, and difficulties finding information are associated with stress, burnout, and increased workload [ 18 , 21 - 25 ]. Because of the increased time spent on EHR-related tasks, physicians report working longer hours and completing documentation outside of work, which further contributes to stress and burnout [ 23 - 25 ].…”
Section: Introductionmentioning
confidence: 99%